Maximizing Online Loyalty: The Mediating Effects of Satisfaction and Trust - Ruslim, Tommy Setiawan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
The significance of customer loyalty in the banking industry has gained more importance, particularly due to the recent technological advancements. With the growing number of emerging digital banking services, customers demand banks to develop mobile banking apps with superior online features and qualities. This study aims to investigate how utilitarian and hedonic qualities impact online loyalty through the mediating roles of online satisfaction and online trust in digital banking services. The study collected responses from 251 digital banking service customers living in Jakarta. The results indicate that hedonic qualities significantly enhance online satisfaction, online trust, and online loyalty. Utilitarian qualities are confirmed to enhance online satisfaction and online trust directly. However, utilitarian qualities are not found to be directly linked to online loyalty. Furthermore, this research concludes that both online satisfaction and online trust mediate the relationships between utilitarian and hedonic qualities and online loyalty.